Diet and gut microbiome: Impact of each factor and mutual interactions on prevention and treatment of type 1, type 2, and gestational diabetes mellitus - Davide Menafra; Mattia Proganò; Nicola Tecce; Rosario Pivonello; Annamaria Colao (Human Nutrition & Metabolism)
The gut microbiota (GM) plays a key role in health by influencing several physiological functions, including the digestive process, the immune system, vitamin production, and mental health. Dysbiosis in gut microbial composition and function has been linked to systemic inflammatory response and the development of metabolic diseases, including diabetes mellitus (DM). ''Leaky gut'' resulting from dysbiosis causes endotoxemia, leading to systemic inflammation and insulin resistance, which are pathogenetic agents of type 2 and gestational DM. Moreover, in children, gut dysbiosis has been associated with the immunitary dysregulation with increased risk of autoimmunity and development of type 1 DM. However, dietary changes in the GM and their role in DM are poorly understood. Plant-based diets that are low in fat and high in fiber have been associated with beneficial effects on the GM. Clinical trials of prebiotics and probiotics have shown promising, albeit mixed, results. This narrative review summarizes recent findings on the relationship between the GM, diet, and DM, focusing on the systems in which the microbiota is involved in the pathogenesis of this disease and its potential use as a therapy. In addition, we discuss immune dysfunction associated with gut dysbiosis and its role in type 1, type 2, and gestational DM. Further research is needed to evaluate the GM as a potential therapeutic target for the prevention and treatment of DM.